Dinamika Kerukunan Antar Umat Beragama Eksistensi Masyarakat Islam di Bali Pasca Bom Bali Tahun 2002-2012 - ., Wildaniyati; Dewi Setiowati Sunaryo, Fransiska (Humanis; Vol 22 No 1 (2018)DO - 10.24843/JH.2018.v22.i01.p19, 2018)
On Saturday 12 October 2002, at Banjar Lagian Kelod, Kuta, the Bali Bombing explosion occurred. This is an early event that becomes a long struggle between crisis and harmony. The crisis that occurred as a threat to economy and social harmony that has been built in the Balinese society. Series of bombing incidents is not only of course, but also the cracking of Muslim relations with Hindus in Bali. The several concepts used in this study are collective behavior, norms and corporate actors. The methodology used is the oral history method. Research methods and sources include heuristics, criticism, interpretation and historiography. The results reveal there are some disquiets experienced by Muslim community post bomb, including on the social, security, and economic aspects. Similarly, there are some recovery activities conducted by the Ulama in Bali post Bali Bombing, among others by conducting musyawarah, socialization, pengajian, and other social activities, in this case done to restore confidence and re-recognize the existence of Islamic society post Bali Bombing. Collective behavior, corporate norms and actors are the reasons behind the Balinese attitude towards the Islamic community in the face of Bali Bombing.